2023
DOI: 10.3390/land12020287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Evolution of Land-Use Types in the Qilian Mountains from 1980 to 2020

Abstract: The Qilian Mountains (QMs), located in the northeast part of the Qinghai–Tibetan Plateau in China, have a fragile ecological environment, complex and sensitive climate, and diverse land-cover types. It plays an important role in the “Qinghai–Tibetan Plateau Ecological Barrier” and “Northern Sand Control Belt” in China’s “two screens and three belts” ecological security strategy. Based on land use data of 1980, 1990, 1995, 2000, 2005, 2010, 2015, and 2020, we utilized GIS technology, land use dynamic degree, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The common land use in the Dayekou Basin in the Qilian Mountains of China, as evidenced by the published literature, is primarily grassland. Multiple studies conducted over different periods have consistently identified grassland as the dominant land use type in this region [21,22]. Additionally, there is a presence of construction land, farmland, unused land, and woodland, though these cover smaller proportions compared to the grassland.…”
Section: Study Areamentioning
confidence: 97%
“…The common land use in the Dayekou Basin in the Qilian Mountains of China, as evidenced by the published literature, is primarily grassland. Multiple studies conducted over different periods have consistently identified grassland as the dominant land use type in this region [21,22]. Additionally, there is a presence of construction land, farmland, unused land, and woodland, though these cover smaller proportions compared to the grassland.…”
Section: Study Areamentioning
confidence: 97%
“…These data represent the latest generation of this data type. The ERA5 model combines observational data using physical laws to produce a dataset that covers specific areas and periods [27]. The current study used precipitation data from ERA5-Land with a 0.25 • × 0.25 • spatial resolution.…”
Section: Datamentioning
confidence: 99%
“…The dynamic degree is based on the desert (oasis) area, reflecting the magnitude and rate of change of the desert (oasis) area in different periods, including single dynamic degree and comprehensive dynamic degree [34,[39][40][41][42].…”
Section: Dynamic Degreementioning
confidence: 99%
“…The comprehensive dynamic degree is the ratio of the total decrease (or total increase) of each class (referring to oasis or desert) in the region to two times the total area of the regional land class [34,41]. The model reflects the magnitude and rate of change in the overall land use type (referring to oasis or desert) area over the study period, and the formula is as follows:…”
Section: Dynamic Degreementioning
confidence: 99%
See 1 more Smart Citation